A NEW NEMATODE CAMALLANUS BOOMKERI SP. FROM THE FISH, CHANNA ORIENTALIS ( O ESTIECHTHYES: CHANNIDAES) IN FRESHWATERS OF PANJGUR, BALOCHISTAN - A. Kakar; F. M. Bilqees; A. Iqbal; M. A. Panezai; G. E. S. Mukhtar (Journal of Animal and Plant Sciences, 2013)
The present study was conducted to investigate the helminth parasites of fish. During this study a new species of genus Camallanus Railliet and Henry, 1915 (Nematoda: Camallanidae) is described from specimens found in the swim bladder of Channa orientalis Bloch and Schneider, 1801 collected from River Gwarko in Panjgur (Balochistan).This new species Camallanus boomkeri n. sp. differs from other reported forms of the genus on the basis of number of longitudinal ridges, body measurements and the caudal end of both sexes. It may also be differed in tridents nature, length of spicules and anal papillae number in males, and by the inflation of vulva lips in females and excretory pore position.
Keywords: Nematode; Camallanus boomkeri n. sp.; freshwater fish; Channa orientalis